2016
DOI: 10.1080/01443615.2016.1174838
|View full text |Cite
|
Sign up to set email alerts
|

Human immune deficiency virus (HIV) infection during pregnancy at Gadarif hospital, Eastern Sudan

Abstract: This was a prospective study conducted on all pregnant and parturient women attending Gadarif Maternity Hospital, Sudan from January 2009 to December 2013 to investigate the maternal characteristics, pregnancy outcomes and estimate of maternal to child transmission of HIV among HIV infected women. During the study period, there were 26 HIV positive mothers among 6420 tested women yielding an incidence rate of 0.4%. The majority of these 26 infected women were of urban residence (69.2%), presented with normal C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…The total sample size of participants was 15,479. Based on information retrieved from these studies; HIV prevalence ranged from 0 to 18.3% among different study populations, 75% of studies (9/12) reported a prevalence lower than 3% (0.7% [ 10 ], 1.3% [ 11 ], 1.5% [ 12 ], 0% [ 14 ], 0.4% [ 15 ], 0.3% [ 17 ], 0.9% [ 19 ], 0.7% [ 20 ] and 1.2% [ 21 ]), while 25% (3/12) of studies reported a prevalence equal or higher than 3% (3% [ 18 ], 5.7% [ 13 ], and 18.3% [ 16 ]). The result of meta-analysis; (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The total sample size of participants was 15,479. Based on information retrieved from these studies; HIV prevalence ranged from 0 to 18.3% among different study populations, 75% of studies (9/12) reported a prevalence lower than 3% (0.7% [ 10 ], 1.3% [ 11 ], 1.5% [ 12 ], 0% [ 14 ], 0.4% [ 15 ], 0.3% [ 17 ], 0.9% [ 19 ], 0.7% [ 20 ] and 1.2% [ 21 ]), while 25% (3/12) of studies reported a prevalence equal or higher than 3% (3% [ 18 ], 5.7% [ 13 ], and 18.3% [ 16 ]). The result of meta-analysis; (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies reported HIV prevalence among pregnant women in Sudan, one study was conducted in Kassala, Eastern Sudan [ 17 ], three in Khartoum State [ 11 , 12 , 14 ], and one in Gadarif State [ 15 ]. The prevalence rates ranged from 0 to 1.4%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies from Sudan and Iran [39,41,42,49] suggested that WLHIV experienced high-risk pregnancy and stressful perinatal events post-HIV diagnosis. The Sudan study by Adam and colleagues [39] found that respondents had higher rates of anaemia during pregnancy, spontaneous preterm births, and neonatal deaths than the control group of HIV-negative women. Pregnant Iranian WLHIV commonly experienced psychological distress concerning the impact of pregnancy on their health and that of their baby [41,42,49].…”
Section: Perinatal Experiences and Outcomesmentioning
confidence: 99%
“…The majority of the Sudanese, Iranian, and Turkish WLHIV participating in the reviewed studies reported they had acquired HIV through sexual contact with their husband/partner with many expressing concern regarding their sexual life and satisfaction post-diagnosis [39,41,47,49,51]. Studies in Bangladesh, Iran, and Morocco suggested that most WLHIV remained married and sexually active [40,44,49].…”
Section: Sexual Satisfaction and Life After Hivmentioning
confidence: 99%